Web Log Mining of Server Log Data of ‘Counselling Website’ Using Microsoft Excel and Implementation of Preprocessing Algorithm - et. al., Neeraj Kandpal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Web log mining is essential for the generation of useful patterns from web log data. Web log mining is an indispensable tool to improve website services and servers performance. It gives valuable information to website administrators for the advancement of performance of a website. Web log data mining is possible from a wide variety of available tools. We have introduced a method for web log mining using Microsoft Excel. In this paper we have used different features of Microsoft Excel like macros, pivot tables, filtering tools, graphical tools for preprocessing of web log data. A preprocessing algorithm is proposed for data cleaning of web log data using these features. These preprocessed web log files used for pattern discovery and pattern analysis. After data preprocessing various usage patterns generated to reveal actual behaviour of visitors at the time of traversal at website ‘rajeducon.com’. Various patterns are also generated for raw web log data using Microsoft Excel.